Effect of different spectral processing methods on the quantitative model of Astragalus polysaccharides detected by NIR spectroscopy - ZHAO, Fan; ZHANG, Jiawei; ZHI, Jihao; YAN, Zhaoru (Food Science and Technology, 2023)
Quality control of Chinese herbal medicines requires reliable and rapid detection techniques, Many scholars have used NIR spectroscopy for research in Chinese herbal medicine industry. The aim of this study was to evaluate the feasibility of combining NIR spectroscopy and machine learning to predict the adulteration content of Astragalus polysaccharides. The astragalus polysaccharide and rice flour were mixed to form astragalus polysaccharide adulterant with different concentration. the Quantitative prediction models are built using the support vector machine (SVM). Different pre-processing methods of SG, SNV, WT, SG+SNV, SG+WT were used to process the spectra, and then the continuous projection algorithm (SPA) and uninformative variable elimination (UVE) were used to select the characteristic wavelengths. The SVM prediction model based on SG+SNV+SPA is optimal with an RPD of 2.653, indicating that the model has good predictive ability. The results showed that NIR technique could be used for quantitative analysis of Astragalus polysaccharides.